Delivery or expectant management for prevention of adverse maternal and neonatal outcomes in hypertensive disorders of pregnancy: an individual participant data meta‐analysis. (2nd April 2019) - Bernardes, T. P.; Zwertbroek, E. F.; Broekhuijsen, K.; Koopmans, C.; Boers, K.; Owens, M.; Thornton, J.; van Pampus, M. G.; Scherjon, S. A.; Wallace, K.; Langenveld, J.; van den Berg, P. P.; et al.
ABSTRACT: Objective: Hypertensive disorders affect 3–10% of pregnancies. Delayed delivery carries maternal risks, while early delivery increases fetal risk, so appropriate timing is important. The aim of this study was to compare immediate delivery with expectant management for prevention of adverse maternal and neonatal outcomes in women with hypertensive disease in pregnancy. Methods: CENTRAL, PubMed, MEDLINE andClinicalTrials.gov were searched for randomized controlled trials comparing immediate delivery to expectant management in women presenting with gestational hypertension or pre‐eclampsia without severe features from 34 weeks of gestation. The primary neonatal outcome was respiratory distress syndrome (RDS) and the primary maternal outcome was a composite of HELLP syndrome and eclampsia. The PRISMA‐IPD guideline was followed and a two‐stage meta‐analysis approach was used. Relative risks (RR) and numbers needed to treat or harm (NNT/NNH) with 95% CI were calculated to evaluate the effect of the intervention. Results: Main outcomes were available for 1724 eligible women. Compared with expectant management, immediate delivery reduced the composite risk of HELLP syndrome and eclampsia in all women (0.8% vs 2.8%; RR, 0.33 (95% CI, 0.15–0.73); I 2 = 0%; NNT, 51 (95% CI, 31.1–139.3)) as well as in the pre‐eclampsia subgroup (1.1% vs 3.5%; RR, 0.39 (95% CI, 0.15–0.98); I 2 = 0%). Immediate delivery increased RDS risk (3.4% vs 1.6%; RR, 1.94 (95% CI 1.05–3.6); I 2 = 24%; NNH, 58 (95% CI, 31.1–363.1)), but depended upon gestational age. Immediate delivery in the 35 th week of gestation increased RDS risk (5.1% vs 0.6%; RR, 5.5 (95% CI, 1.0–29.6); I 2 = 0%), but immediate delivery in the 36 th week did not (1.5% vs 0.4%; RR, 3.4 (95% CI, 0.4–30.3); I 2 not applicable). Conclusion: In women with hypertension in pregnancy, immediate delivery reduces the risk of maternal complications, whilst the effect on the neonate depends on gestational age. Specifically, women with a‐priori higher risk of progression to HELLP, such as those already presenting with pre‐eclampsia instead of gestational hypertension, were shown to benefit from earlier delivery. © 2019 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.